1983
DOI: 10.1111/j.1467-1770.1983.tb00986.x
|View full text |Cite
|
Sign up to set email alerts
|

Interference and Natural Language Processing in Second Language Acquisition

Abstract: This paper reports the findings of a study of the acquisition of relative clauses in Chinese, Japanese, Persian, German, and Portuguese by first and second year students of these languages with English as their first language. Various structures were tested with the aim of separating the features of interlanguage which may be attributed to first language interference from those which may be explained as being universal to second language acquisition. Among these structures were use of resumptive pronouns in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 6 publications
1
31
0
Order By: Relevance
“…From extraction from Verb Phrases (VPs) (object RRCs), L2 learners move to extraction from Prepositional Phrases (PPs) in VPs (object of preposition RRCs). Other studies (Hyltenstam, 1984;Tarallo & Myhill, 1983) have also suggested that the relativization of NP positions lower in the Noun Phrase Accessibility Hierarchy 8 (NPAH) (object of preposition) seems to be more problematic for L2 learners than the relativization of NP positions higher in the NPAH (direct object). Therefore, not surprisingly, Greek learner performance in object of preposition RRCs is not as successful as English native performance.…”
Section: Discussionmentioning
confidence: 99%
“…From extraction from Verb Phrases (VPs) (object RRCs), L2 learners move to extraction from Prepositional Phrases (PPs) in VPs (object of preposition RRCs). Other studies (Hyltenstam, 1984;Tarallo & Myhill, 1983) have also suggested that the relativization of NP positions lower in the Noun Phrase Accessibility Hierarchy 8 (NPAH) (object of preposition) seems to be more problematic for L2 learners than the relativization of NP positions higher in the NPAH (direct object). Therefore, not surprisingly, Greek learner performance in object of preposition RRCs is not as successful as English native performance.…”
Section: Discussionmentioning
confidence: 99%
“…Shorter distance implies a less complex derivation than in cases where the distance between the filler and the gap is longer. Linear distance has been discussed in relation to the subject/object asymmetry in L1 (de Villiers et al 1979;Clancy et al 1986;Diessel & Tomasello 2005;and Hsu et al 2009, among others) and L2 acquisition (Tarallo & Myhill 1983;R. Hawkins 1989), as well as in adult processing studies (Gibson's 1998(Gibson's , 2000 Dependency Locality Theory (DLT); J.…”
Section: Hypotheses For the Subject Vs Object Asymmetry In Rcsmentioning
confidence: 97%
“…It seems counterintuitive, however, to posit that grammatical interrogative sentences are all equal from the point of view of the learner. There is empirical evidence to suggest that structures such as interrogatives and relative clauses are not acquired uniformly by L2 learners (e.g., Tarallo and Myhill, 1983;Hylstenstam, 1984;Hawkins, 1989, for restrictive relative clauses; Myles, 1990;1994, for interrogatives and agreement). Even if movement is technically the same operation in all interrogatives and relatives, the learner has to operate under real-time constraints, and with a limited processing capacity.…”
Section: )mentioning
confidence: 98%
“…Before describing the study undertaken in order to test this hypothesis, the findings of a number of SLA studies of a related area of syntax, restrictive relative clauses, will be summarized. These studies (e.g., Gass, 1983;Tarallo and Myhill, 1983;Hyltenstam, 1984;Pavesi, 1986) have investigated whether relativizing a direct object (DO) would be easier or more difficult than the relativization of, say, an oblique object (00) or a genitive (Gen.), and they have suggested that performance in the L2 is linked to the syntactic function of the wh-phrase. These studies have concluded that the Accessibility Hierarchy (AH) of noun-phrases as defined by Keenan and Comrie (1977) on the basis of the typology of relative clauses in the world's languages is a predictor of difficulty in SLA.2 2 Figure 6 Level 4 and above 2 The AH is based on a hierarchy of grammatical relations on the basis of crosslinguistic distribution and expresses the relative accessibility to relativization of NP positions, as follows: Subject (S): 'the lady who -likes snails'; direct object (DO): 'the car that he rented -'; indirect object (IO): 'the children to whom he gave some toys -'; oblique object (OO): 'the boy about whom he heard so many lies -'; genitive (Gen.): 'the girl whose jumper I borrowed -' ; object of a comparison (OComp.…”
Section: )mentioning
confidence: 98%